PENGARUH LAMA FERMENTASI TERHADAP KUALITAS KIMIA SUSU SAPI YANG DIFERMENTASI MENGGUNAKAN SCOBY: THE EFFECT OF FERMENTATION DURATION ON THE CHEMICAL QUALITY OF COW'S MILK FERMENTED USING SCOBY - Ramadhan Diprameswara; Ludfia Windyasmara (Tropical Animal Science, 2026)
Milk is a highly nutritious food; however, its near-neutral pH and high nutrient content make it highly susceptible to microbial spoilage. Fermentation is an effective processing method to improve milk stability and quality through microbial activity. This study aimed to evaluate the effect of fermentation time on the chemical quality of cow’s milk fermented using Symbiotic Culture of Bacteria and Yeast (SCOBY). The research was conducted using an experimental design with fermentation times of 0, 2, 4, 6, 8, and 10 days at room temperature (±28 °C). The chemical parameters analyzed included pH, total titratable acidity, and viscosity. The results showed that fermentation time significantly affected the chemical characteristics of SCOBY-fermented cow’s milk. Increasing fermentation time led to a progressive decrease in pH and a significant increase in total titratable acidity due to the accumulation of organic acids produced by microbial metabolism. Viscosity exhibited significant changes during fermentation, characterized by a decrease at the early fermentation stage followed by an increase at longer fermentation times, which was associated with acid-induced protein destabilization and partial coagulation. In conclusion, fermentation time plays a crucial role in determining the chemical quality and rheological properties of cow’s milk fermented with SCOBY. It is recommended that fermentation time be carefully controlled to obtain fermented milk products with optimal chemical quality and acceptable physicochemical characteristics.